Układy outsourcingowe czy nowa forma prowadzenia działań gospodarczych? - Niemczyk, Jerzy (Outsourcing networks - a new form of operating business?, 2005)
Outsourcing networks are the specific kind of interorganizational networks based on the outsourcing concept. The goal of the article is to prove, that such objects should be treated as a new form of operating business. In the article outsourcing networks were compared to such concepts as holding, alliance and co-operational systems. The results of the analysis show, that outsourcing networks, although contain some elements of the concepts mentioned above, are in fact a new form of organization of activities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 305-313